Management of Posttraumatic Posterior Elbow Defects by Nonmicrosurgical Reconstruction - Pawar, Manoj Dinkar; Sahasrabudhe, Parag; Panse, Nikhil; Bindu, Ameya Rajan; Phulwer, Rohit Dagadu (Indian Journal of Plastic Surgery, 2022)
Introduction Reconstruction of posterior defects is challenging due to the quality and uniqueness of the excess skin at the elbow that is durable, thick, pliable, and without much subcutaneous tissue. The goal of reconstruction is to cover the elbow defects with a durable skin cover that will facilitate full passive range of motion. In this era of microsurgery, free tissue transfer is feasible for almost any defect. However, in this article, we discuss various locoregional and pedicled flap options and the protocol followed at our institute to tackle posttraumatic posterior elbow defects.Materials and Methods This is a retrospective analysis of 48 patients with posttraumatic posterior elbow defects admitted from January 2012 to February 2020. Posterior elbow defects were assessed according to the size and location and managed with a nonmicrosurgical reconstruction.Results Of 48 patients, 32 were managed with nonmicrosurgical flaps. Eighteen patients had large defects and 14 had small defects. Reverse lateral forearm flap was the workhorse flap for defect coverage. Of 32 flaps, nine developed complications; however, no patient had total flap necrosis.Conclusion Posterior elbow defects are a difficult problem to tackle. To achieve optimal results, all patients with elbow trauma should be attended and managed by orthopaedic and plastic surgeons in collaboration for optimal results. We believe that most of these defects can be resurfaced by nonmicrosurgical reconstruction with proper planning and execution and their utility cannot be understated.
Keywords: posterior elbow defects; classification of elbow defects; nonmicrosurgical reconstruction; management of posterior elbow defects; elbow defects